Unique crack behaviors of glass BK7 occurred in successive double scratch under critical load of median crack initiation. Issue 8 (July 2020) - Feng, Junyuan; Wan, Zhenping; Wang, Wei; Huang, Xiaofang; Ding, Xinrui; Tang, Yong
Abstract: Successive double scratch tests under the critical load of median crack initiation were conducted to investigate the crack behaviors under the influence of interaction between the arranged grits during grit-arranged grinding BK7 glass. After the inspection of the subsurface crack morphology by the advanced focused ion beam, it is found that with the separation distance increasing, the crack behaviors under the 2nd scratch experience three stages: a new type of crack—premature lateral crack initiation, no crack initiation and median crack reappearing. The crack behaviors that occurred in the former two stages can alleviate the subsurface damage. The initiation mechanisms of the unique crack behaviors were analyzed by a stress field analytical model. Also, the benefit of these unique crack behaviors on the grinding process was discussed.